#### Answer

$2i \sqrt{6}$

#### Work Step by Step

$\sqrt{-24} = \sqrt{-1} \cdot \sqrt{24} = \sqrt{-1} \cdot \sqrt{6 \cdot 4} = 2i \sqrt{6}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$2i \sqrt{6}$

$\sqrt{-24} = \sqrt{-1} \cdot \sqrt{24} = \sqrt{-1} \cdot \sqrt{6 \cdot 4} = 2i \sqrt{6}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.